Extramural venous invasion detected by MDCT as an adverse imaging feature for predicting synchronous metastases in T4 gastric cancer. (April 2017) - Cheng, Jin; Wu, Jing; Ye, Yingjiang; Zhang, Chunfang; Zhang, Yinli; Wang, Yi
Background: Extramural venous invasion (EMVI) is defined histologically as the active invasion of tumor cells to the lumens of mesenteric vessels beyond the muscularis propria in advanced gastrointestinal cancer, resulting in distant metastases. Purpose: To determine the association between synchronous metastatic disease in patients with T4 gastric cancer and EMVI detected on contrast-enhanced multiple-row detector computed tomography (MDCT). Material and Methods: A total of 152 patients with T4 gastric carcinoma were retrospectively reviewed and divided into EMVI-positive and EMVI-negative groups where EMVI, as detected on MDCT, was defined as a tubular or nodular soft tissue thickening extending from the tumor along the vessels of the mesentery. Synchronous metastases were detected by MDCT and/or confirmed by postoperative diagnosis. Logistic regression analyses were performed to analyze the predictive factors of synchronous metastases in gastric cancer. Results: Synchronous metastases were found in 47 of 152 (30.9%) patients with T4 gastric cancer. Thirty-one of 77 (40.3%) patients in the EMVI-positive group had evidence of metastases compared to 16 (21.3%) of 75 patients in the EMVI-negative group ( P = 0.019). Synchronous metastases were significantly associated with EMVI with an odds ratio (OR) of 2.250 (95% CI, 1.072–4.724). Conclusion: EMVI-positive tumors, as an adverse imaging feature, were significantly associated with synchronous metastases in patients with T4 gastric cancer.